Pengenalan Langkah-Langkah Polya pada Pemecahan Masalah Matematika untuk Materi SPLTV Siswa Kelas X SMA Manda Elu - Lede, Yulius; Moza, Florida; Kami, Kanisius; Zogara, Leonard (CV. Global Cendekia Inti, 2025)
The problem raised is about solving mathematical story problems using Polya's steps. The material presented is a system of linear equations in three variables (SPLTV). The activity was carried out in the form of a seminar for students of class X SMAS Manda Elu which will be held in April 2025. The stages of implementing this activity are preparation, implementation and evaluation. The preparation stage is preparing SPLTV material which is completed using Polya's steps with the team to be delivered to community service partners. At the seminar implementation stage, the speaker provided material to 28 students with the core material, namely SPLTV story problems which are solved using Polya's steps, namely understanding the problem, making a plan, implementing the plan and making conclusions. Furthermore, the evaluation stage of this activity is carried out by giving practice questions to students and students are also asked for their responses regarding the community service activities that have been carried out.